Acclimatization and efficacy of different transport systems for reducing stress of hilsa (Tenualosa ilisha) seeds during transportation: Hilsa seed transportation - Chattopadhyay, D. N.; Ray, P. K.; Chakraborty, A.; Mandal, R. N. (Journal of the Inland Fisheries Society of India, 2023)
Acclimatization and efficacy of different transport systems for hilsa (Tenualosa ilisha) seeds were evaluated. Different criteria such as nets used for capture, durations, containers, stocking-densities, air and oxygen filled polyethylene bags, temperature, locations and salinity were tested. Wild fry caught with lift net showed higher (P